THU0420 A citrullinated and MMP degradated vimentin neoepitope as a novel rheumatic biomarker. (23rd January 2014) - Vassiliadis, E.; Maksymowych, W.P.; Zhang, C.; Duffin, K.L.; Christiansen, C.; Leeming, D.J.; Karsdal, M.A.; Bay-Jensen, A.C.
Abstract : Background: Autoantibodies against citrullinated vimentin (Anti-CCP) are present in rheumatic diseases years before clinical onset, albeit in a subset of patients. Artificial antigens against such auto antibodies have been successfully used for diagnostics through utilization of anti-CCP tests. However, these artificial antigens are not known to be expressed in vivo in the diseased tissue and hence be part of the pathogenesis. Objectives: To evaluate whether a citrullinated and MMP degraded fragment of vimentin, produced by proteolytic activity of MMP-2 and -8 and identified by mass spectrometry in human cartilage, could be used as a rheumatic marker. Methods: Vimentin peptide 69'-RLRSSVPGVR-78' was identified by MS in human cartilage as being generated by MMP-2 and-8. The sequence was modified by substituting the C terminal arginine with a Citrulline moiety and a monoclonal antibody against the sequence RLRSSVPGV-Citrulline (VICM) was developed.A competitive ELISA assay was developed.VICM was evaluated in two well characterised clinical cohorts consisting of Ankylosing spondylitis (AS) (n=57) and rheumatoid arthritis (RA) (n=48) pre and post anti-TNF treatment (2 and 3 months respectively) compared with 40 healthy controls. Results: The antibody was found to be specific for citrullinated and MMP-degraded vimentin with no reactivity to the arginine rich sequence or intact vimentin. Mean intra and inter assay variation was determined to be 2.69% and 6.57% respectively. LLOD and lower limit of quantitation LLOQ was determined to be 0.076ng/ml and 0.431ng/ml respectively. Mean systemic VICM levels were found to be 3.6ng/ml in the control group. Pre TNF treatment, mean geometric VICM levels in the AS cohort was found to be 13.9ng/ml (P<0.0001, 256.4% increase, ROC=0.81), while in the RA cohort VICM was found to be 20.3ng/ml (P<0.0001, 443.5% increase, ROC=0.80).Post TNF treatment, VICM marker geometric mean level was reduced to 8.5ng/ml (P<0.0001) representing a 38.8% (P>0.01) reduction for the AS cohort and 14.6ng/ml (P<0.001) representing a 31.1% (P>0.05) reduction for the RA cohort. Conclusions: Serological levels of the citrullinated MMP-2 and-8 cleaved fragment of vimentin were statistically significantly increased in both cohorts compared with healthy controls. VICM levels statistically significantly reduced as a response to TNF therapy. Normally, AS is considered an anti-CCP negative disease, and our data challenge this paradigm – as high levels of citrullinated peptides were present. Whether this is merely a sensitivity issue or have a deeper biological impact on the understanding of the common denominators of AS and RA pathology needs to be carefully investigated. As opposed to synthetic antigens used in the anti-CCP tests, the base of this competitive assay is a vimentin peptide found in vivo via mass spectrometry which was MMP-2 and -8 cleavage specific. Thus, this fragment, among others, may be used as an indicator of the in vivo matrix remodeling which occurs during pathology progression. This novel marker may in combination with existing markers provide additional valuable information for rheumatic disease patient assessment. Disclosure of Interest: None Declared